2019
DOI: 10.1016/j.jad.2018.12.100
|View full text |Cite
|
Sign up to set email alerts
|

An inflammatory profile linked to increased suicide risk

Abstract: Background: Suicide risk assessments are often challenging for clinicians, and therefore, biological markers are warranted as guiding tools in the assessments. Suicidal patients display increased cytokine levels in peripheral blood, although the composite inflammatory profile in the subjects is still unknown. It is also not yet established whether certain inflammatory changes are specific to suicidal subjects. To address this, we measured 45 immunobiological factors in peripheral blood and identified the biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 70 publications
3
63
0
Order By: Relevance
“…Relevantly, the genetic overlap between IL-8 and risk for suicide attempts was significant in females but not males. According to Keaton et al [34], the biological profile of patients considered to be at increased risk of suicide differed from that of depressed individuals. Importantly, blood cell count and polymorphonuclear leukocyte count had a significant impact on suicide risk.…”
Section: Studies Analyzing Inflammatory Abnormalities In Suicidal Patmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevantly, the genetic overlap between IL-8 and risk for suicide attempts was significant in females but not males. According to Keaton et al [34], the biological profile of patients considered to be at increased risk of suicide differed from that of depressed individuals. Importantly, blood cell count and polymorphonuclear leukocyte count had a significant impact on suicide risk.…”
Section: Studies Analyzing Inflammatory Abnormalities In Suicidal Patmentioning
confidence: 99%
“…However, based on the selected studies and in line with a previously published paper of our research group upon the same topic [7], the existence of an association between inflammatory cytokines abnormalities and suicidal behavior does not necessarily reflect a specific causal link. Among the selected studies, eleven reports [8,9,12,[25][26][27][28][29][30][31][32] analyzed inflammatory cytokines abnormalities in suicidal patients, four [33][34][35][36] explored cytokines abnormalities in patients with both a positive history of suicide attempts and suicidal ideation, two [37,38] investigated the existence of inflammatory cytokines abnormalities levels in depressed patients with suicidal ideation vs. those abnormally without, seven [31,[40][41][42][43][44]50] examined the inflammatory cytokines abnormalities in patients with a history of suicide attempts vs. those without, three [45][46][47] analyzed patients died by suicide vs. those died for other causes, and two [48,49] focused on depressed suicidal patients with suicidality.…”
Section: Summary Of Main Findings and Review Of Study Designsmentioning
confidence: 99%
“…Previous studies have suggested an association between inflammation and increased suicide risk in people with a psychiatric illness [36], but whether the association between CMV infection and suicide exists is uncertain. Previous research in this area has found increased levels of inflammatory markers (e.g., interleukin-6) in patients with suicidal ideation and behaviour [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated pro-inflammatory cytokines have been found in blood and cerebrospinal fluid and postmortem brain samples from suicidal patients, 25 indicating that inflammation may contribute to the pathophysiology of suicide. 28,29 Several studies reviewed for this article show the existence of a high prevalence of lifetime suicidal ideation, suicidal behavior, attempted, and completed suicide in patients with psoriasis in comparison with not only normal subjects but with subjects suffering from other dermatological conditions as well. [30][31][32] As the association between psoriasis and psychiatric comorbidity, including suicide and risk of self-harm, has been vastly reported in the literature, a right and early psoriasis treatment improves the mental condition, particularly depression and anxiety.…”
Section: Psoriasis and Depressionmentioning
confidence: 98%